Interlingual Transfer In The English Of Students At Sman 2 Praya - Muhammad Sarifuddin; Rosidah Alawiyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
This research is aimed to identify the types of error that the sudents make in doing the interlingual transfer and to identify the sources of interlingual transfer. This research was conducted at the second grade students XI.MIPA.1 of SMAN 2 Praya in academic year 2018/2019. The research method used descriptive qualitative method. There were 32 students taken as the subject who comprised 15 females and 17 males. The instruments of the reseach were structed interview and questionnaire. Structed interview was used to find the students error in doing the in interlingual transfer. There were three types of error that the students committed; Omission, Addition, and Misformation. The studensts tend to their first language structure. For the questionnaire, the researcher found the sources of interlingual transfer that the students committed. There were three sources of interlingual tranfer that the students mostly committed in their daily spoken such as; pressure to perform, limited L2 environment, and monitor use and the use of the L1. Based on above, it concluded that the students often commit the interlingul transfer in their daily communication.